DC's legends of tomorrow. The complete third season [videorecording (DVD)] - Berlanti, Greg; Guggenheim, Marc; Kreisberg, Andrew, 1971-; Klemmer, Phil (Warner Bros. Home Entertainment Inc., 2018)
After defeating the Legion of Doom, the heroes face a new threat created by their actions. By revisiting a moment in time that they had already participated in, they've essentially fractured the timeline and created anachronisms all across time! In Season Three, the Legends must find a way to return all the anachronisms to their original timelines before the time stream falls apart.